Effects of personalized invitation letters on research participation among general practitioners: a randomized trial - Patrick Hennrich; Christine Arnold; Michel Wensing (BMC Medical Research Methodology, 2021)
Abstract Background Participation of general practitioners is crucial for health care studies. However, recruiting them is an ongoing challenge and participation rates of general practitioners around the globe are often low. One feasible and cost-efficient approach to potentially enhance participation rates among general practitioners are personalized invitation letters, since they may increase one’s attention to and appreciation of a study. Still, evidence whether this method actually affects participation is scarce and ambiguous in relation to physicians. Methods We undertook a randomized trial in a sample of general practitioners from three German states in the context of a large, observational study on physicians’ coordination and uptake of recommended cardiovascular ambulatory care. An intervention group (n = 757 general practitioners) received a personalized invitation to participate in the observational study, the control group (n = 754 general practitioners) received a generic invitation. Both groups were blinded to group assignment. Eventual participation rates as well as the number and types of responses overall were compared between arms. Besides the main intervention, sociodemographic and geographical context factors were considered as well. Results The overall participation rate among physicians was 2.6% (2.8% in the intervention group and 2.4% in the control group). No statistically significant effect of personalization on participation of physicians was found (relative risk to participate when receiving a personalized invitation of 1.17 [95%-CI: 0.62, 2.21]). However, the number of responses to the invitation varied significantly between the geographical regions. Conclusions Personalization of first written contact alone did not improve research participation among general practitioners, which was overall very low. Trial registration The study in which the trial was embedded has been registered prospectively at the German Clinical Trials Register (DRKS) under registration number DRKS00019219 .